Internal Hernia Masquerading As Necrotizing Enterocolitis - Kylat, Ranjit I. (Frontiers in Pediatrics, 2017)
In extremely preterm infants’, acute abdominal emergencies are fortunately less common with improving care. Spontaneous intestinal perforation (SIP) and necrotizing enterocolits (NEC) are conditions where emergent surgery is most often needed. Conservative medical management and placement of temporary drain are often used in the initial management. Internal hernias (IH) are an uncommon cause of bowel obstruction in neonates, are difficult to diagnose and unfortunately are found only at autopsy. The presentation in preterm infants, distinction between these conditions and the need for early diagnosis of IH is discussed.